2022
DOI: 10.20473/jafh.v11i2.33307
|View full text |Cite
|
Sign up to set email alerts
|

Protein content of Spirulina sp. Cultured Using a Combination of Urea and TSP Fertilizers

Abstract: This study aims to determine the effect of the combined use of Urea and TSP fertilizers on the Protein content of Spirulina sp. This research was conducted for 10 days at the Center for Brackish Water Aquaculture (BPBAP) Takalar. The method used in this study is an experimental design with Completely Randomized Design (CRD) using 4 treatments with 3 replications, namely Treatment A (0.4 g/l Urea + 0.008 g/l TSP), B (0.5 g/l Urea + 0.010 g/l TSP), C (0.6 g/l Urea + 0.012 g/l TSP) and D (0.4 g/l Urea + 0.008 g/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is supported by the research which reported that Spirulina sp. has a nutritional profile containing high crude protein content (59%-63% of dry weight) (Suherman and Arsad, 2022), phycobiliproteins -the pigment-protein complex such as C-phycocyanin (C-PC), phycoerythrin (PE) and allophycocyanin (APC), which are rich in antioxidant activity (Lafarga et al, 2020). Spirulina sp.…”
Section: Shrimp Growthmentioning
confidence: 99%
“…This is supported by the research which reported that Spirulina sp. has a nutritional profile containing high crude protein content (59%-63% of dry weight) (Suherman and Arsad, 2022), phycobiliproteins -the pigment-protein complex such as C-phycocyanin (C-PC), phycoerythrin (PE) and allophycocyanin (APC), which are rich in antioxidant activity (Lafarga et al, 2020). Spirulina sp.…”
Section: Shrimp Growthmentioning
confidence: 99%